Pelatihan Media Pembelajaran dengan Teknologi Google Assistant sebagai Inovasi KBM Sekolah Luar Biasa di Jakarta - Ika Nurlaili Isnainiyah; Ati Zaidiah; Artika Arista (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
The development of IT-based learning media in the field of education continues to progress in order to create comprehensive and interesting Teaching and Learning Activities (TLAs). In accordance with the Master Plan for Persons with Disabilities (RIPD) of the Ministry of Social Affairs of the Republic of Indonesia, learning media innovations are also important to be implemented in special schools for students with special needs in Indonesia. Innovation in learning media at SLBN 01 Jakarta still encounters obstacles, especially related to the lack of understanding of user experience in the teaching and learning process between teachers and students with special needs. Therefore, the team from the Faculty of Computer Science, UPN Veteran Jakarta (UPNVJ) conducted community service activities (PkM) to provide Google Assistant-based Learning Media Training to the Teacher Group from SLBN 01 Jakarta. The results of the activity aim to enable the Jakarta SLBN 01 Teacher Group to be able to independently apply the Google Assistant-based Natasha Bot learning media based on directions and assistance from the PkM team. The results of the feedback obtained from the participants indicated that the activity was going very well. The results also show an increase in teachers' knowledge in Special Schools (SLB) in the application of Google Assistant-based trivia quiz learning media innovations for Indonesian language subjects at the 6th grade elementary school level.